Cover. Issue 8 (11th August 2019) - Andacoglu, Oya M.; Himmler, Amber; Geng, Xue; Ahn, Jaeil; Ghasemian, Seyed; Cooper, Matthew; Abrams, Peter
Abstract : The cover image is based on the Original Article* Comparison of Glycemic Control after Pancreas Transplantation for Type 1 and Type 2 Diabetic Recipients at a High Volume Center by Oya Andacoglu** et al., https://doi.org/10.1111/ctr.13656